LYVE-1 identifies asthma and drives PDGF-BB-induced proliferation, migration, and oxidative stress in airway smooth muscle cells via the PI3K/Akt pathway - Tang, Yunbo; Zhou, Nan; Ni, Xiaohui (Frontiers in Pharmacology, 2026)
BackgroundAsthma is a chronic inflammatory airway disease characterized by airflow limitations, airway remodeling, and immune dysregulation. Lymphatic vessel endothelial hyaluronan receptor-1 (LYVE-1) has recently been implicated in inflammatory and remodeling processes in the body. However, its clinical significance and mechanistic role in asthma are unclear. This study aimed to investigate the association between soluble LYVE-1 (sLYVE-1) levels and asthma severity, airway inflammation, and remodeling, and to elucidate its regulatory role in airway smooth muscle cell (ASMC) activation via the PI3K/Akt signaling pathway.MethodsA total of 238 participants were enrolled, including 80 healthy controls, 72 patients with asthma who were in remission, and 86 patients with acute asthma. Clinical characteristics, pulmonary function parameters, inflammatory and remodeling biomarkers, and serum sLYVE-1 levels were assessed. Correlation analyses were performed to evaluate the relationship between sLYVE-1 and disease-related parameters. Mechanistic studies were conducted in vitro using platelet-derived growth factor-BB (PDGF-BB)-stimulated ASMCs with LYVE-1 knockdown to explore the downstream signaling and functional effects.ResultsSerum sLYVE-1 levels were significantly elevated in patients with asthma and progressively increased with disease severity. sLYVE-1 levels were inversely correlated with forced expiratory volume in one second (FEV1) and FEV1/FVC and positively correlated with total immune globulin E (IgE), eosinophil counts, T-helper cell type 2 (Th2) and T-helper cell type 17 (Th17) cell proportions, fractional exhaled nitric oxide (FeNO), type 2 cytokines, and airway remodeling-associated mediators, including vascular endothelial growth factor A (VEGF-A), stromal-derived factor 1α (SDF-1α), transforming growth factor-β1 (TGF-β1), matrix metalloproteinases-9 (MMP-9), and hyaluronan (all p < 0.001). In vitro, LYVE-1 silencing markedly attenuated PDGF-BB-induced PI3K/Akt phosphorylation, ASMC proliferation and migration, extracellular matrix-related gene expression, and pro-inflammatory cytokine secretion while reducing oxidative stress and enhancing antioxidant activity.ConclusionElevated circulating sLYVE-1 levels are closely associated with asthma severity, airway inflammation, and airway remodeling. Mechanistically, LYVE-1 promoted PDGF-BB-induced ASMC activation through PI3K/Akt signaling, highlighting LYVE-1 as a potential biomarker and potential therapeutic target for asthma.